(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2005)
The bryophyte flora of the NNP “Desnyansko-Starohutsky” ( the Sumy region, NE Ukraine) includes 102 species of 56 genera, 34 families belonging to two divisions: Marchantiophyta (9 spp.) and Bryophyta (93 spp.). Among them Brachythecium reflexum (Starke) B.S.G. and B. starkei (Brid.) B.S.G. are new for the whole Ukrainian Polissya, Calypogeia neesiana (Mass. et Carest.) K.Mull. and Orthotrichum diaphanum Brid. – new for the Left Bank Ukrainian Polissya; a number of the others are rare ones for the mentioned territories.